MEDIA PERMAINAN KARTU HURUF DALAM PEMBELAJARAN BAHASA PADA PENDIDIKAN ANAK USIA DINI - Tri Ariyani (UNISAN JURNAL, 2024)
This exploration expects to portray plans to further develop perusing abilities for youth through word game exercises at TKIT Bung Tomo Indonesia, Damai Town, Bandar Lampung. Portray the most common way of further developing the perusing abilities of small kids through word game exercises at TKIT Bung Tomo Indonesia, Damai Locale, Bandar Lampung. Depict the aftereffects of further developing the perusing abilities of youth through word game exercises at TKIT Bung Tomo Indonesia, Damai Region, Bandar Lampung. In the mean time, the examination approach utilizes a subjective methodology. This subjective methodology is utilized to depict occasions, local area conduct, or conditions in specific spots exhaustively and top to bottom in story structure. The exploration strategies that the creator utilized in this examination were: perception, meetings, documentation and writing study. In light of the consequences of the exploration and conversation depicted in the past part, the accompanying ends can be drawn; Utilizing proper learning media will encourage youngsters’ pleasure and interest in an idea or understanding and can foster kids’ learning inspiration. Instructors can work on the improvement of youngsters’ perusing abilities through word games, perusing urges kids to tune in and talk, so kids can figure out how to peruse, practice how to peruse with word games and animate youngsters to act and mimic. So that kids’ perusing skills can be accomplished ideally, systems and approaches are required that are in accordance with the attributes of learning in Kindergarten, to be specific utilizing fun techniques utilizing word cards to foster youngsters’ abilities to understand and including youngsters straightforwardly in understanding exercises. Figuring out how to peruse utilizing word games can further develop the ability to peruse of class B kids at TKIT Bung Tomo Indonesia, Damai Region, Bandar Lampung, which should be visible in the ability to peruse of youngsters separately and in gatherings and the youngsters’ mental fortitude to show up before others. class